Simulation of Flux Distributions on the Foam Absorber with Solar Reactor for Thermo-chemical Two-step Water Splitting H2 Production Cycle by the 45 kWth KIER Solar Furnace. (May 2015) - Cho, H.S.; Gokon, N.; Kodama, T.; Kang, Y.H.; Kim, J.K.
Abstract: The flux distributions on the device in the solar reactor with the solar furnace were studied. This study aims to understand of characters of concentrated sun rays through KIER solar furnace and design of device shape for uniform heat distribution on the device surface. For the calculation of heat flux on the device with the KIER solar furnace, the optical modeling program Soltrace was used. At first, the KIER 45 kWth solar furnace and flat disk type device shape was simulated for understand of past experimental results. And then 3 cylinder shape device model and 1 conical shape device model was suggested and the heat flux intensity on the device was calculated. Finally, 5 models which is including flat disk type device shape, 3 cylinder shape, and 1 conical shape device models was calculated and compared. The results show that the concentrated sun rays from dish and heat flux intensity are has a directional characteristic concentrated to normal direction than perpendicular direction. The results will be applied to next solar demonstrations which are design of new solar reactor and new device shape.